The Influence of Response Speed and Information Quality on the Effectiveness of SME Sales Through Facebook - Ramadhani, Indah; Dailami, D.; Widiya, Ulva; Yunita, Irma; Nurhuda, Ridha; Mutia, M. (Manunggal Halim Jaya, 2026)
This study aims to study the effect of response speed and quality of information provided in the customer service system via Facebook on the effectiveness of Mama Donuts' SME sales. Data were collected through surveys and analysis using statistical methods to test the effect of each variable both partially and simultaneously. From the analysis conducted, it was found that both response speed and information quality have a positive and significant impact on sales effectiveness. Partially, it was found that with a faster response time, better information to help answer questions significantly increased sales effectiveness with a significant value (sig) of less than 0.05. Simultaneously, both variables have a strong influence with a correlation coefficient value of 0.906 and an R2 of 81.6%. This means that these variables can explain most of the variability in the effectiveness of Mama Donuts' SME sales. These results strengthen the argument that faster responses and better information quality positively impact Facebook sales effectiveness, thus providing a sales performance strategy for SMEs.